AVALIAÇÃO DE DANOS NO DNA E RADICAIS LIVRES EM TRABALHADORES RURAIS EXPOSTOS A AGROTÓXICOS - SANTOS, GREICE F. F. D.; GUECHEVA, TEMENOUGA N.; ROCHA, JOÃO B. D.; GOETTEMS, PAULINE B.; BELLINASO, MARIA D. L. (Salão do Conhecimento, 2013)
Resumo